Anxiety Levels in Pre-Exodontia Children with Topical Anesthesia in Class III A and III B Students: Tingkat Kecemasan Anak Pra Tindakan Exodontia Dengan Topikal Anestesi Pada Siswa-Siswi Kelas III A Dan III B - Bagus Maulidi; Neny Setiawaty Ningsih; Asmaul Husna; Budi Suryana (Dental Therapist Journal, 2022)
In providing an optimal dental health service, one of which is tooth extraction, this action given to children often causes pain and discomfort in children. Pain control is not only beneficial for children, but also for dental health workers. Because the calmness of the child will make it easier for dental health workers to carry out tooth extractions calmly, easily and according to the proper procedure. This study aims to describe the level of anxiety in pre-exodontia children with topical anesthesia at SDN 15 North Pontianak District in 2015. The design in this study was descriptive with a cross-sectional approach, ie each object of the study was observed at the same time and only done once. The results of the study on the level of anxiety in pre-exodontia children with topical anesthetics in grade III A and III B students at SDN 15 North Pontianak District in 2015, that of the 48 respondents who experienced a lot of anxiety levels were severe anxiety levels, namely 31 respondents (64 ,6%). The most who experienced it were girls as many as 25 respondents (52.1%). Based on the age category, the level of anxiety in pre-exodontia children with topical anesthesia at SDN 15 North Pontianak in 2015 was 9 years old with a total of 22 respondents (45.8%). Meanwhile, from the gender category, the level of anxiety in pre-exodontia children with topical anesthesia was mostly girls, namely 25 respondents, with a distribution of 15 respondents experiencing severe anxiety levels, 9 respondents experiencing moderate anxiety levels and none experiencing mild anxiety levels. Dalam memberikan suatu pelayanan kesehatan gigi yang optimal salah satunya adalah pencabutan gigi, tindakan ini diberikan kepada anak sering menimbulkan rasa sakit dan ketidaknyamanan pada anak. Pengendalian rasa sakit ini tidak hanya menguntungkan bagi anak, tetapi juga bagi tenaga kesehatan gigi. Karena ketenangan anak akan memudahkan tenaga kesehatan gigi dalam melakukan pencabutan gigi dengan tenang, mudah dan sesuai prosedur yang seharusnya. Penelitian ini bertujuan untuk mendeskripsikan tingkat kecemasan anak pra tindakan exodontia dengan topikal anestesi di SDN 15 Kecamatan Pontianak Utara Tahun 2015. Rancangan dalam penelitian ini bersifat deskriptif dengan pendekatan cross-sectional yaitu setiap objek penelitian dilakukan observasi pada saat yang bersamaan dilakukan sekali saja. Hasil penelitian tingkat kecemasan anak pra tindakan exodontia dengan topikal anestesi pada siswa-siswi kelas III A dan III B di SDN 15 Kecamatan Pontianak Utara pada tahun 2015, bahwa dari 48 responden yang banyak mengalami tingkat kecemasan adalah tingkat kecemasan berat yaitu sebanyak 31 responden (64,6%). Paling banyak yang mengalaminya adalah anak perempuan sebanyak 25 responden (52,1%). Berdasarkan dari kategori umur tingkat kecemasan anak pra tindakan exodontia dengan topikal anestesi di SDN 15 Pontianak Utara tahun 2015 yang banyak mengalami adalah umur 9 tahun dengan jumlah responden 22 orang sebanyak (45,8%). Sedangkan dari kategori jenis kelamin tingkat kecemasan anak pra tindakan exodontia dengan topikal anestesi, yang paling banyak adalah anak perempuan yaitu 25 responden, dengan distribusi 15 responden mengalami tingkat kecemasan berat, 9 responden mengalami tingkat kecemasan sedang dan tidak ada yang mengalami tingkat kecemasan ringan.